Comparison of the materno-fetal transfer of fifteen structurally related bisphenol analogues using an ex vivo human placental perfusion model. (August 2021) - Gély, Clémence A.; Lacroix, Marlène Z.; Morin, Mathieu; Vayssière, Christophe; Gayrard, Véronique; Picard-Hagen, Nicole
Abstract: Regulatory measures and public concerns regarding bisphenol A (BPA) have led to its replacement by a variety of alternatives in consumer products. Due to their structural similarity to BPA, these alternatives are under surveillance, however, for potential endocrine disruption. Understanding the materno-fetal transfer of these BPA-related alternatives across the placenta is therefore crucial to assess prenatal exposure risks. The objective of the study was to assess and compare the placental transfer of a set of 15 selected bisphenols (BPs) (BP 4-4, BPA, BPAF, BPAP, 3-3 BPA, BPB, BPBP, BPC, BPE, BPF, BPFL, BPM, BPP, BPS and BPZ) using the ex vivo human placental perfusion model. The UHPLC–MS/MS method for simultaneous quantification of these BPs in perfusion media, within a concentration range of 0.003–5 μM, was able to measure placenta transfer rates as low as 0.6%–4%. Despite their structural similarities, these BPs differed greatly in placental transport efficiency. The placental transfer rates of BP4-4, BPAP, BPE, BPF, 3-3BPA, BPB, BPA were similar to that of antipyrine, indicating that their main transport mechanism was passive diffusion. By contrast, the placental transfer rates of BPFL and BPS were very limited, and intermediate for BPBP, BPZ, BPC, BPM, BPP and BPAF, suggesting weak diffusional permeability and/or that their passage might involve efflux transport. These placental transfer data will be particularly useful for predicting the fetal exposure of this important class of emerging contaminants. Graphical abstract: Image 1 Highlights: The efficiency of placental transport differs greatly between bisphenols. BP4-4, BPAP, BPE, BPF, 3-3BPA, BPB, BPA cross placenta by simple diffusion. Materno-fetal transfer of BPFL and BPS is very limited.